The Prevention Strategy of the Sambinae Subdistrict Leader Against Drug Trafficking - Sartika, Renni; Nurfarhati; Syamsuddin; Mas'ud; Kasman (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2025)
This study evaluates the drug prevention strategies implemented by the Head of Sambinae Subdistrict and identifies key barriers affecting their effectiveness. Using qualitative descriptive method, data was collected through observation, in-depth interviews, and document analysis. The findings reveal that the strategies are effective due to strong collaboration between the subdistrict office, Bhabinkamtibmas, Babinsa, community leaders, religious figures, and the National Narcotics Agency (BNN). The integration of Soft Power, Hard Power, and Smart Power approaches enhances the impact of prevention efforts. Optimal resource allocation including facilities, personnel, and funding and effective coordination and further support implementation. However, challenges such as limited human resources, geographical constraints, and low community participation persist. Legal reinforcement through Law No. 35 of 2009 and informal educational programs, such as the Anti-Drug Peer Youth initiative, are crucial in raising awareness. Multisectoral collaboration remains a key factor in the sustainable prevention of drug circulation in the Sambinae Subdistrict.